Adenosine receptor 2B activity promotes autonomous growth, migration as well as vascularization of head and neck squamous cell carcinoma cells. Issue 1 (9th January 2020) - Wilkat, Max; Bast, Hanna; Drees, Robert; Dünser, Johannes; Mahr, Amelie; Azoitei, Ninel; Marienfeld, Ralf; Frank, Felicia; Brhel, Magnus; Ushmorov, Alexey; Greve, Jens; Goldberg‐Bockhorn, Eva; et al.
Abstract : Adenosine is a signaling molecule that exerts dual effects on tumor growth: while it inhibits immune cell function and thereby prevents surveillance by the immune system, it influences tumorigenesis directly via activation of adenosine receptors on tumor cells at the same time. However, the adenosine‐mediated mechanisms affecting oncogenic processes particularly in head and neck squamous cell carcinomas (HNSCC) are not fully understood. Here, we investigated the role of adenosine receptor activity on HNSCC‐derived cell lines. Targeting the adenosine receptor A2B (ADORA2B) on these cells with the inverse agonist/antagonist PSB‐603 leads to inhibition of cell proliferation, transmigration as well as VEGFA secretion in vitro . At the molecular level, these effects were associated with cell cycle arrest as well as the induction of the apoptotic pathway. In addition, shRNA‐mediated downmodulation of ADORA2B expression caused decreased proliferation. Moreover, in in vivo xenograft experiments, chemical and genetic abrogation of ADORA2B activity impaired tumor growth associated with decreased tumor vascularization. Together, our findings characterize ADORA2B as a crucial player in the maintenance of HNSCC and, therefore, as a potential therapeutic target for HNSCC treatment. Abstract : What's new? The adenosinergic system plays an important role in the development of many types of cancer. However, the underlying mechanisms remain poorly understood. This study set to identify the oncogenic function of the adenosine receptor 2B (ADORA2B) in head and neck squamous cell carcinoma (HNSCC)‐derived tumor cells. The results show that ADORA2B is upregulated and constitutively active in HNSCC‐derived cell lines. This activity is sufficient to promote autonomous cell growth, migration, and angiogenesis in vitro and in vivo . The data suggest ADORA2B as an important biomarker and potential therapeutic target for the treatment of HNSCC and other ADORA2B‐expressing solid tumors.